2023
DOI: 10.1038/s41586-023-06508-4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial sensing of AHR ligands regulates intestinal homeostasis

Abstract: Endothelial cells line the blood and lymphatic vasculature, and act as an essential physical barrier, control nutrient transport, facilitate tissue immunosurveillance and coordinate angiogenesis and lymphangiogenesis1,2. In the intestine, dietary and microbial cues are particularly important in the regulation of organ homeostasis. However, whether enteric endothelial cells actively sense and integrate such signals is currently unknown. Here we show that the aryl hydrocarbon receptor (AHR) acts as a critical no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Recent single-cell RNAseq data of intestinal endothelial cells show high homeostatic expression of Plvap , especially in capillaries ( Kalucka et al, 2020 ; Tan et al, 2023 ; Wiggins et al, 2023 ), consistent with its induction in response to VEGFA ( Strickland et al, 2005 ) and its role as a functional component of fenestrae diaphragms, which are readily observed in gut capillaries ( Bernier-Latmani et al, 2022b ; Casley-Smith, 1971 ; Casley-Smith et al, 1975 ; Milici and Bankston, 1981 ; Palay and Karlin, 1959 ; Stan et al, 2012 ). These diaphragms promote vessel barrier function as mice with germline and endothelial Plvap ablation and patients with PLVAP mutations display leaky intestinal vessels and edema ( Elkadri et al, 2015 ; Stan et al, 2012 ).…”
Section: Intestinal Vessel Pathologymentioning
confidence: 60%
See 2 more Smart Citations
“…Recent single-cell RNAseq data of intestinal endothelial cells show high homeostatic expression of Plvap , especially in capillaries ( Kalucka et al, 2020 ; Tan et al, 2023 ; Wiggins et al, 2023 ), consistent with its induction in response to VEGFA ( Strickland et al, 2005 ) and its role as a functional component of fenestrae diaphragms, which are readily observed in gut capillaries ( Bernier-Latmani et al, 2022b ; Casley-Smith, 1971 ; Casley-Smith et al, 1975 ; Milici and Bankston, 1981 ; Palay and Karlin, 1959 ; Stan et al, 2012 ). These diaphragms promote vessel barrier function as mice with germline and endothelial Plvap ablation and patients with PLVAP mutations display leaky intestinal vessels and edema ( Elkadri et al, 2015 ; Stan et al, 2012 ).…”
Section: Intestinal Vessel Pathologymentioning
confidence: 60%
“…These vessels are more dilated, sparse, and less branched than vessels in the villus/crypt zone (unpublished data). Recent single-cell RNA sequencing (RNAseq) data reveals that these vessels express genes for fat ( Cd36 , Fabp5 ) and water and glycerol ( Aqp1 , Aqp7 ) transport similar to those observed in muscle- and white adipose tissue–specific endothelial cells ( Fan et al, 2021 ; Kalucka et al, 2020 ; Wiggins et al, 2023 ), suggesting they perform nutrient transport to support intestinal smooth muscle metabolism.…”
Section: Intestinal Organizationmentioning
confidence: 86%
See 1 more Smart Citation
“…The provision of a bespoke Cyp1a1 ‘knock-in’ reporter mouse line that accurately portrays the dynamics of AHR signalling longitudinally in vivo, will be of considerable value in evaluating the impacts and duration of repeated challenge in individual animals. Although in these studies we have used concentrations of AHR ligands that were defined by others 72 , 80 82 , our observation that Cyp1a1 luminescence was induced in animals maintained on control diets but switched to a non-SPF facility, suggests that this model can detect endogenously-generated and physiologically relevant AHR activity. That said, it is also important to recognise that ex vivo Cyp1a1 mRNA analysis and Cyp1a1 -luciferase-based luminescence offer slightly different read-outs of AHR activity.…”
Section: Discussionmentioning
confidence: 99%
“…In a Huntington’s disease model, Ahr deletion led to protection against neurotoxicity and oxidative stress 80 . Recent studies also reported the role of endothelial AhR signaling in integrating dietary cues to maintain tissue homeostasis 81 and exerting protective function in the gut-lung axis 82 . AhR is also important for timely termination of the regenerative response of intestinal epithelia by restricting chromatin accessibility of regeneration-associated Yap/Tead target genes in colonic stem cells 83 .…”
Section: Discussionmentioning
confidence: 99%